STUDY PERILAKU PEMILIH DALAM PEMILIHAN KEPALA DESA (PILKADES) DI DESA DAYUN KECAMATAN DAYUN KABUPATEN SIAK PERIODE 2013-2019 - Kartika Kusuma Astuti; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Village Head Election was a competition arenas open to the village head candidate. The determination of the voter's choice of candidates chosen is a phenomenon that can be observed trends influencing factors including voting behavior in village elections (the elections). At previous period dayun village was a village with low community participation, but in the period 2013 - 2019 this community was so enthusiastic about participating in the elections. From the results of the elections and the results obtained are absolute victory by one of the candidates who are still younger and have not been in the government order dayun villageThe problems discussed this thesis that is how the the behavior of voters in the election of the village head and the factors driving change in the political behavior of the citizens of the Dayun Village Dayun District of Siak Sriindrapura Regency. This research uses descriptive quantitative research study was a survey form. Technique of determining the number of samples used was to use the formula Slovenian. Respondents were sampled in this study were 96 respondentsThe results showed that there was a change in the behavior of voters in the elections in the Dayun village of period 2013 - 2019. The factors that encourage behavioral change is people tend to judge one of the candidates for village head has a personality that is reliable, has a vision / mission clear, good image, education level, age, village head candidate, religious similarities and figure a good candidate.Key Word : Behavior, Village Head Election and Village Head